ANALISIS PENGEMBANGAN PERPUSTAKAAN POJOK BACA DALAM MENINGKATKAN LITERASI BACA DI KELAS TINGGI SDN 10 BILAH BARAT DESA TEBING LINGGAHARA - Mila Nirmala Sari Hasibuan, Elysa Rohayani Hsb, Lily Rohanita Hasibuan, Rahmi Nazliah, Rosmidah Hasi (PT.JNDI, JURNAL BIMA, 2025)
This study aims to describe and analyze the development of the corner library in improving reading literacy at the 10 West Elementary School in the village of Cliff Lingga Hara. This study uses a descriptive qualitative research method with a case study approach. Data collection techniques were carried out by interviewing, observing, and documenting the principal, teachers, and students. The data were analyzed using an interactive model consisting of data reduction, data display, and verification. Checking the validity of the data is done by increasing the persistence of observations and triangulation. The process of developing a literacy culture is carried out through three stages, namely: (1) planning for developing a literacy culture, manifested in the form of goal formulation, program formulation, strategy formulation, and management of facilities and infrastructure. (2) implementation of literacy culture development. The implementation of literacy culture development consists of habituation, development, and teaching processes. (3) evaluation is carried out in the form of weekly, monthly, and annual evaluations. The results of the study indicate that the implications of developing a literacy culture can increase the interest, interest, and interest in reading in students.